Asymptomatic primary infection with Epstein-Barr virus: observations on young adult cases - Abbott, RJ; Pachnio, A; Pedroza-Pacheco, I; Leese, AM; Begum, J; Long, HM; Croom-Carter, H; Stacey, A; Moss, PAH; Hislop, AD; Borrow, P; Rickinson, AB; et al. (American Society for Microbiology, 2017)
Epstein-Barr virus (EBV) is typically acquired asymptomatically in childhood. By contrast, infection later in life often leads to infectious mononucleosis (IM), a febrile illness characterised by anti-EBV IgM antibody-positivity, high loads of circulating latently-infected B cells, and a marked lymphocytosis caused by hyper-expansion of EBV-specific CD8+ T cells plus milder expansion of CD56dim NKG2A+ KIR– NK cells. How the two situations compare is unclear due to the paucity of studies on clinically-silent infection. Here we describe five prospectively-studied asymptomatic infections identified in a sero-epidemiological survey of University entrants. In each case the key blood sample had high cell-associated viral loads without marked IM-like CD8 lymphocytosis or NK cell disturbance. Two of the highest viral load cases showed a coincident expansion of activated EBV-specific CD8+ T cells but overall CD8+ T cell numbers were either unaffected or only mildly increased. Two slightly lower load cases, which serology suggests may have been caught earlier in the course of infection, also showed no T or NK cell expansion at the time. Interestingly, in another higher load case where T and NK cell responses were undetectable in the primary infection bleed, EBV-specific T cell responses did not appear until several months later, by which time virus loads in the blood had already fallen. Thus some asymptomatic primary infections have very high circulating viral loads and a cell-mediated immune response that is qualitatively similar to IM but of lower magnitude. However, others may be quite different and ultimately could reveal novel mechanisms of host control.